Implementation Of Agile Methodology In Patient Medical Records Management At Dental Clinics: Analysis Of Pilot Testing And User Acceptance Evaluation - Sihombing, Denny Jean Cross (Jurnal Ekonomi, 2024)
This research aims to identify and analyze Agile solutions in patient medical record management at dental clinics. With a focus on developing Agile-based applications, this research involves stages of user needs analysis, application development, and user acceptance evaluation. A pilot test method is employed to test the application in randomly selected dental clinic environments. At the same time, user acceptance evaluation is conducted to measure the system's effectiveness in meeting user needs and improving workflow efficiency. The research findings indicate that implementing Agile solutions significantly enhances system responsiveness to changes, improves communication between clinic staff and patients, and enhances overall user satisfaction. This study makes a significant contribution to the development of information technology solutions focusing on user needs in the healthcare sector.